2019
DOI: 10.5114/reum.2019.87615
|View full text |Cite
|
Sign up to set email alerts
|

Tossing and turning with degenerative arthropathy: an assessment of poor sleep quality in knee osteoarthritis

Abstract: ObjectivesTo determine the frequency and predictors of sleep abnormalities among patients with knee osteoarthritis (OA) in Nigeria.Material and methodsA multi-centre, hospital-based, cross-sectional study, involving 250 knee OA patients. Consenting patients 18 years and above, who satisfied the American College of Rheumatology (ACR) criteria for knee OA were recruited from five Nigerian tertiary centres over 3 months. An interviewer-administered questionnaire was used to collect demographic and relevant clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“… 29 Two studies from Nigeria reported the same patient population of men and women ≥18 years of age with knee OA who were assessed according to whether they had depression 13 or poor sleep quality. 14 WOMAC pain subscale scores were significantly worse in patients with knee OA and depression ( p <0.0001), 13 neuropathic pain ( p <0.001), 29 or poor sleep quality ( p <0.001), 14 compared to those with knee OA with no depression, no neuropathic pain, or normal sleep quality.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“… 29 Two studies from Nigeria reported the same patient population of men and women ≥18 years of age with knee OA who were assessed according to whether they had depression 13 or poor sleep quality. 14 WOMAC pain subscale scores were significantly worse in patients with knee OA and depression ( p <0.0001), 13 neuropathic pain ( p <0.001), 29 or poor sleep quality ( p <0.001), 14 compared to those with knee OA with no depression, no neuropathic pain, or normal sleep quality.…”
Section: Resultsmentioning
confidence: 94%
“… 14 WOMAC pain subscale scores were significantly worse in patients with knee OA and depression ( p <0.0001), 13 neuropathic pain ( p <0.001), 29 or poor sleep quality ( p <0.001), 14 compared to those with knee OA with no depression, no neuropathic pain, or normal sleep quality.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The PSQI is a legacy instrument that has been used to study prevalence of poor sleep and associated factors in a wide range of patients with rheumatologic diagnoses, including systemic lupus erythematosus (SLE) (30–32), RA (33–36), spondyloarthritides (37–39), systemic sclerosis (28,33), Sjögren syndrome (40,41), osteoarthritis (42–44), and fibromyalgia (45,46). It may not be able to detect well‐known disturbances of sleep that accompany aging (25).…”
Section: Pittsburgh Sleep Quality Indexmentioning
confidence: 99%